INOVASI PENANGANAN DOWNTIME SYSTEM KOMPUTER DALAM UPAYA MENINGKATKAN EFEKTIVITAS PELAYANAN PASIEN DI RUMAH SAKIT ANUGERAH MEDICAL CENTRE METRO - Windi Pertiwi; Mia Elviana; M Saka Praja Dinata; Azzra Atsila Sutanto; Kaella Violina (Journal of Hospital Administration and Excellent Health Service, 2026)
Introduction: The implementation of Hospital Management Information Systems (HMIS) and Electronic Medical Records (EMR) has significantly improved healthcare service efficiency. However, system downtime remains a major challenge affecting patient registration and service continuity. This study aimed to analyze the causes of computer system downtime and develop innovative strategies to improve patient service effectiveness at Anugerah Medical Centre Hospital Metro. Method: A qualitative descriptive approach was employed through observation, in-depth interviews, documentation, and Focus Group Discussions. The Urgency, Seriousness, and Growth (USG) method was used to prioritize problems, while Fishbone Analysis identified root causes. Results: Computer system downtime emerged as the highest priority problem. Root causes included obsolete hardware, lack of preventive maintenance, limited maintenance budgets, absence of downtime SOPs, and insufficient user competence. Proposed innovations consisted of standardized downtime SOPs, scheduled preventive maintenance, equipment monitoring dashboards, staff training, and digital incident reporting. These interventions are expected to reduce downtime frequency, accelerate recovery time, and improve service efficiency. Conclusion: Comprehensive downtime management innovation improves the reliability of hospital information systems and supports better patient service quality.